2022
DOI: 10.1108/jabs-09-2021-0376
|View full text |Cite
|
Sign up to set email alerts
|

Influence of contextual factors on investment decision-making: a fuzzy-AHP approach

Abstract: Purpose The behavioural decision-making process of individuals highlights the importance of investors’ sentiment and their correlation with the real economy. This paper aims to contribute to the literature of behavioural finance by examining the influence of contextual factors on investment decision-making. Design/methodology/approach Using a questionnaire, a total of 445 valid responses were collected from March to May 2021 through online sources. The current study uses a technique of Fuzzy-analytical hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 101 publications
2
66
0
1
Order By: Relevance
“…However, since rational investors have access to only partial knowledge and do not follow proper techniques, they prefer to make satisfying rather than perfect investment selections; as a consequence, investment options have become opportunities rather than logical or rational judgments ( Berthet, 2022 ; Qamruzzaman, 2022 ). Investors are expected to make logical judgments, but their possibilities are limited by cognitive capacity, which includes values, routines, knowledge, reflexes, and external environmental elements; the influence of these factors has hampered the decision-making process ( Ahmad and Wu, 2022 ; Sachdeva et al, 2022 ). On the other hand, psychologists have suggested that individuals are not nearly as rational as economists think.…”
Section: Introductionmentioning
confidence: 99%
“…However, since rational investors have access to only partial knowledge and do not follow proper techniques, they prefer to make satisfying rather than perfect investment selections; as a consequence, investment options have become opportunities rather than logical or rational judgments ( Berthet, 2022 ; Qamruzzaman, 2022 ). Investors are expected to make logical judgments, but their possibilities are limited by cognitive capacity, which includes values, routines, knowledge, reflexes, and external environmental elements; the influence of these factors has hampered the decision-making process ( Ahmad and Wu, 2022 ; Sachdeva et al, 2022 ). On the other hand, psychologists have suggested that individuals are not nearly as rational as economists think.…”
Section: Introductionmentioning
confidence: 99%
“…Advocate recommendations comprising suggestions from relatives, friends, family, brokers, financial planners, news channels, and so on. carry considerable weight in investing decisions, albeit to a lesser extent than the company's reputation and financial and neutral information, aligning with existing literature (Ali & Tariq, 2013; Brijlal, 2007; Khawaja & Alharbi, 2021; Sachdeva & Lehal, 2023). As highlighted by Hoffmann et al (2006), these social interactions play a significant role by mitigating uncertainty surrounding investing decisions.…”
Section: Discussionsupporting
confidence: 80%
“…Khawaja and Alharbi (2021) noted that while all five factors of investment decisions were significantly related to investor behavior, neutral information was the most important factor among others for Saudi investors. Sachdeva and Lehal (2023) found all five variables to be influencing the investment decisions of Indian investors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another factor of investors' investment behavior are the contextual factors. Sachdeva et al [44] revealed that a few of contextual factors such as accounting information, self-image or firm-image coincidence, and neutral information are having the greatest influence in the decision-making process of investing. Meanwhile, Hamidon and Kehelwalatenna [45] found out that one of the contextual factors of investment on trading, namely stockbroker's recommendations, caused in lower investment performance because there was a lower level of financial returns once investors tried to invest by imitating on other investors' behavior whilst trading on stock broker's recommendations.…”
Section: Contextual Factors Of Investment Biases In Cryptocurrencymentioning
confidence: 99%